PROBLEMATIKA HUKUM TANAH MASJID TANPA SERTIFIKAT DAN IKRAR WAKAF: STUDI KASUS MASJID AL UKHUWWAH PANYILEUKAN. - Fajri Rizki Fathony; Lena Ishelmiany Ziaharah; Ahmad Damiri (LPPM STAI Muhammadiyah Probolinggo, 2026)
The use of land as a mosque in community practice is often carried out without a clear legal status regarding ownership, transfer of rights, or a valid waqf pledge (ikrar wakaf), which may lead to legal uncertainty and potential disputes, particularly when the land originates from third parties or private legal entities. This study aims to analyze the juridical status of the land of Al Ukhuwwah Mosque in Panyileukan, which has factually been used as a public place of worship but is not supported by a Waqf Pledge Deed (Akta Ikrar Wakaf) or a valid legal basis for the transfer of land rights. The analysis is based on the theory of legal certainty to assess the extent to which the absence of a legal basis for the transfer of rights affects the legal protection and recognition of mosque land, both under positive law and Islamic law. This research employs an empirical juridical approach with a descriptive analytical method. Data were collected through interviews, field observations, and documentation studies, and were analyzed by linking empirical facts with the legal provisions on waqf and the principles of Islamic family law. The results show that the land of Al Ukhuwwah Mosque is legally not categorized as waqf land and is still recorded as an asset of a private legal entity, indicating that its control is de facto rather than de jure. The main issue lies in the absence of a legal basis for the transfer of land rights, resulting in the lack of legal certainty over the mosque land and the potential for disputes in the future.